2015
DOI: 10.1111/zph.12177
|View full text |Cite
|
Sign up to set email alerts
|

Hybrids of Shigatoxigenic and Enterotoxigenic Escherichia coli (STEC/ETEC) Among Human and Animal Isolates in Finland

Abstract: Diarrhoeagenic Escherichia coli (DEC) cause serious foodborne infections in humans. Total of 450 Shigatoxigenic E. coli (STEC) strains isolated from humans, animals and environment in Finland were examined by multiplex PCR targeting the virulence genes of various DEC pathogroups simultaneously. One per cent (3/291) of the human STEC and 14% (22/159) of the animal and environmental STEC had genes typically present in enterotoxigenic E. coli (ETEC). The strains possessed genes encoding both Shiga toxin 1 and/or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
52
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 31 publications
3
52
1
2
Order By: Relevance
“…STEC/ETEC hybrid strains carrying both stx and est have been isolated from humans and animals (6,(27)(28)(29)(30). Of those, O101:H-isolated from an infant with HUS carried stx2a, estA1, eae, and espP; O2:H27 isolated from a child with diarrhea, an asymptomatic adult, and bovine feces carried stx2a, estA1, and astA (27,28); and O2:H2 isolated from cattle carried stx1a, estA1, and astA (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…STEC/ETEC hybrid strains carrying both stx and est have been isolated from humans and animals (6,(27)(28)(29)(30). Of those, O101:H-isolated from an infant with HUS carried stx2a, estA1, eae, and espP; O2:H27 isolated from a child with diarrhea, an asymptomatic adult, and bovine feces carried stx2a, estA1, and astA (27,28); and O2:H2 isolated from cattle carried stx1a, estA1, and astA (27,29).…”
Section: Discussionmentioning
confidence: 99%
“…Although discrete lineages of ETEC have been identified in high-resolution genomic analysis, ETEC strains are considerably diverse genetically (22,23). Various genome comparison studies using core genome multilocus sequence typing (MLST) (19), MLST based on six genes (7), or pulsed-field gel electrophoresis (16,17) have revealed that hybrid STEC/ETEC genomes are also quite diverse. In addition to strains belonging to the Escherichia coli species, hybrid Shiga toxin-producing Escherichia spp./ETEC strains have been identified that are classified phylogenetically as Escherichia sp.…”
mentioning
confidence: 99%
“…An additional recent report of an E. coli strain isolated from a child with acute diarrhea describes the strain as an enteropathogenic E. coli/ETEC hybrid since the genome contains the locus of enterocyte effacement (LEE) pathogenicity island and a gene encoding LT (11). STEC/ETEC hybrid pathotype strains, carrying a gene expressing Shiga toxin and a gene expressing ST, have been isolated from many sources, including humans, animals, food, and water (4,(12)(13)(14)(15)(16)(17)(18). Some STEC/ETEC hybrid strains have been associated with diarrheal disease and HUS in humans (14,17,19), whereas others have been associated with diarrheal disease in pigs (13,20).…”
mentioning
confidence: 99%
“…Delivery of heat-labile (LT) and/or heat-stable (ST) enterotoxins and release of lipopolysaccharide (LPS) to the intestine are critical virulence traits for the onset of the diarrhea. Moreover, ETEC and other diarrheagenic E. coli strains (e.g., enteropathogenic E. coli [EPEC] and verocytotoxigenic E. coli [VTEC]) may obtain additional virulence factors via horizontal gene transfer (4,5). Formation of attachment and effacing (A/E) lesions on intestinal cells is related to the presence of intimin (eae gene) secreted by EPEC/ETEC (6).…”
mentioning
confidence: 99%